MANAJEMEN PEMBELAJARAN TAHFIZH AL-QUR’AN DALAM MENCETAK SANTRI BERKARAKTER DI MDTA AL-MASTHURIYAH SUKABUMI - Obi Robi'a Al-Aslami (Adaara: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to describe the management of tahfizh Al-Quran learning in producing students with character at MDTA Al-Masthuriyah Sukabumi. This study uses a qualitative approach in the form of descriptive, data sources obtained through interviews, observations, literature studies and documentation. Analysis of the data used is descriptive analysis. Based on the results of the research at MDTA Al-Mashturiyah Sukabumi, it showed several impacts that were felt after learning tahfizh. Madrasas become more qualified after this program is implemented and become superior. Madrasas try to continue to improve themselves in the midst of increasingly fierce competition and the tahfizh program is one that is offered to parents to want to send their children to MDTA Al-Mashturiyah Sukabumi. While the implications for students are to make students motivated in the learning process, train memory or memorization stronger, and can be used as a basis in living daily life.